E-GOVERNMENT IN INNOVATION AND PUBLIC COMMUNICATION - Ambia B Boestam; Swastiningsih Swastiningsih; Cyntia Dewi Anggraini; Azizah Des Derivanti (Universitas Dharma Wacana, 2025)
Public communication has undergone major transformation since the early stages of digitalization of services as part of innovation. One of the main digital transformations in public communication, especially in government systems, is e-government. This study aims to discuss what e-government really is, what research is related to e-government, and what the practice of e-government applications is. This research is a library study research by taking documentation data about innovation and public communication from various sources. The data presented is in the form of the latest studies regarding innovation, especially in public communication. The data collected in this research will then be analyzed using narrative analysis. Narrative analysis refers to a set of methods for interpreting texts that take the form of exposition. The conclusions in this study show that globally, the implementation of e-government throughout the world still has many challenges, especially in Indonesia. Therefore, many improvements still need to be made and this also requires further study about what and how to improve innovation in e-government